Stochastic Wind-Thermal Power Plants Integrated Multi-Objective Optimal Power Flow - Sundaram Pandya; Hitesh Jariwala (Majlesi Journal of Electrical Engineering, 2024)
The recent state of electrical system comprises the conventional generating units along with the sources of renewable energy. The suggested article recommends a method for the solution of single and multi-objective optimal power flow, incorporating wind energy with traditional coal-based generating stations. In this article, the two thermal power plants are replaced with the wind power plants. The techno-economic analysis are done with this state of electrical system. In proposed work, Weibull probability distribution functions is used for calculating wind power output. A non-dominated sorting based multi-objective moth flame optimization technique is used for the optimization issue. The fuzzy decision-making approach is applied for extracting the best compromise solution. The results are authenticated though modified IEEE-30 bus test system, which is combined with wind and thermal generating plants.